Inhibition of Morphine- and Ethanol-Mediated Stimulation of Mesolimbic Dopamine Neurons by Withania somnifera - Bassareo, Valentina; Talani, Giuseppe; Frau, Roberto; Porru, Simona; Rosas, Michela; Kasture, Sanjay B.; Peana, Alessandra T.; Loi, Eleonora; Sanna, Enrico; Acquas, Elio (Frontiers in Neuroscience, 2019)
Morphine- and ethanol-induced stimulation of neuronal firing of ventral tegmental area (VTA) dopaminergic neurons and of dopamine (DA) transmission in the shell of the nucleus accumbens (AcbSh) represents a crucial electrophysiological and neurochemical response underlying the ability of these compounds to elicit motivated behaviors and trigger a cascade of plasticity-related biochemical events. Previous studies indicate that the standardized methanolic extract of Withania somnifera roots (WSE) prevents morphine- and ethanol-elicited conditioned place preference and oral ethanol self-administration. Aim of the present research was to investigate whether WSE may also interfere with the ability of morphine and ethanol to stimulate VTA dopaminergic neurons and thus AcbSh DA transmission as assessed in male Sprague-Dawley rats by means of patch-clamp recordings in mesencephalic slices and in vivo brain microdialysis, respectively. Morphine and ethanol significantly stimulated spontaneous firing rate of VTA neurons and DA transmission in the AcbSh. WSE, at concentrations (200-400 µg/ml) that significantly reduce spontaneous neuronal firing of VTA DA neurons via a GABAA- but not GABAB-mediated mechanism, suppressed the stimulatory actions of both morphine and ethanol. Moreover, in vivo administration of WSE at a dose (75 mg/Kg) that fails to affect basal DA transmission, significantly prevented both morphine- and ethanol-elicited increases of DA in the AcbSh. Overall, these results highlight the ability of WSE to interfere with morphine- and ethanol-mediated central effects and suggest a mechanistic interpretation of the efficacy of this extract to prevent the motivational properties of these compounds.